2022
DOI: 10.1101/2022.08.31.506125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nicked tRNAs are stable reservoirs of tRNA halves in cells and biofluids

Abstract: Cells can release ribosomes and full-length tRNAs into the extracellular space, but these species are rapidly processed by extracellular RNases into stable rRNA and tRNA-derived fragments (tDRs). These nonvesicular extracellular RNAs (nv-exRNAs) constitute the majority of the extracellular RNAome, but little is known about their function or biomarker potential. The high extracellular stability of most of these fragments is also mechanistically unclear. To interrogate this, we measured the stability of several … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Additionally, 5' tRNA Gly(GCC) fragments in mouse sperm were reported to repress transcription of endogenous retroelements in embryos (Sharma et al 2016). Our finding that most 5' halves of this tRNA exist as nicked tRNA in HEK293A cells, coupled with an independent report in human U-2 OS cells (Costa et al 2023), suggests that, for these and other tRNA halves proposed to have novel functions, it will be important to determine the fraction that is unpaired in the cells under study.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, 5' tRNA Gly(GCC) fragments in mouse sperm were reported to repress transcription of endogenous retroelements in embryos (Sharma et al 2016). Our finding that most 5' halves of this tRNA exist as nicked tRNA in HEK293A cells, coupled with an independent report in human U-2 OS cells (Costa et al 2023), suggests that, for these and other tRNA halves proposed to have novel functions, it will be important to determine the fraction that is unpaired in the cells under study.…”
Section: Discussionmentioning
confidence: 89%
“…However, several RNA species are stable in the extracellular space even when not associated with EVs. These resilient extracellular RNAs include ribonucleoprotein particles (RNPs) such as Ago2/miRNA complexes (Turchinovich et al 2011;Arroyo et al 2011;Geekiyanage et al 2020), and protein-protected RNA fragments (LaPlante et al 2023) derived from the ribosome (Tosar et al 2020(Tosar et al , 2022Costa et al 2023), U2 snRNPs (Tosar et al 2022), and possibly Xist RNPs (Dou et al 2024). Additionally, a population of intrinsically stable nicked tRNAs circulates in human biofluids, probably unprotected or naked (Costa et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Because cell culture experiments are typically done in the presence of FBS, a rich source of RNases, we hypothesized that this could explain the apparent lack of naked exRNA bioactivity (Tosar et al 2020(Tosar et al , 2021Costa et al 2023). To study this, we worked with primary cultures of murine bone marrow-derived cells, differentiated into antigen presenting cells (Helft et al 2015;Na et al 2016).…”
Section: Naked Bacterial Exrna Activates Bmdcs In An Ri-dependent Mannermentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the tRNA cleavage and increased generation of tRNA-derived RNAs (tDRs) in response to cellular stress is a well-known phenomenon [Thompson et al, 2008]. However, the Tosar group has recently demonstrated that tRNA halves or tDRs can in fact be produced during RNA isolation from denaturation of full-length “nicked” tRNAs [Costa et al, 2022]. In any case, the absence of full-length tRNAs in libraries from both untreated and SARS-CoV-2-infected cells indicates that the utilized small RNA-seq kit failed to incorporate them into the final NGS library.…”
Section: Discussionmentioning
confidence: 99%